Development And Evaluation Of Multiplex Real-Time Pcr For Porcine Dna Detection In Processed Food - Tan, Lee Lee (2018)
Meat processing is a method of enhancing the flavour or preserving the meat but now it was misused by food manufacturers, whereby the expensive meats in the processed food are substituted with cheaper or inferior meats for their economic gain. Complex composition of processed food today has made the species determination a more difficult task. A simple and practical procedure for identification of meat species origin in processed meat products was developed, whereby a SYBR Green-based duplex real-time polymerase chain reactions (qPCR) approach coupled with a rapid DNA extraction method was developed to detect Sus scrofa DNA in processed food. The qPCR targeted LINE-1, a repetitive element sequence exclusively found in pig genome, together with an internal control based on 16S ribosomal RNA gene. The assay was validated for 1) specificity, 2) sensitivity and 3) robustness on processed meat products. Results showed that assay was highly specific when evaluated against a panel of commonly consumed species. The developed assay is capable of capturing the DNA of 0.001% (w/w) adulterated pork meat in just one and a half hour. A total of 121 commercial meat products were tested. No pork adulteration was detected in all the halal-labelled samples. Similar results were obtained using both developed method and kit. The assay would be particularly useful as an alternative for pork control test in food industry